A Theory of Bank Regulation and Management Compensation - John, Kose; Saunders, Anthony; Senbet, Lemma W. (Review of Financial Studies, 2000)
We show that concentrating bank regulation on bank capital ratios may be ineffective in controlling risk taking. We propose, instead, a more direct mechanism of influencing bank risk-taking incentives, in which the FDIC insurance premium scheme incorporates incentive features of top-management compensation. With this scheme, we show that bank owners choose an optimal management compensation structure that induces first-best value-maximizing investment choices by a bank's management. We explicitly characterize the parameters of the optimal management compensation structure and the fairly priced FDIC insurance premium in the presence of a single or multiple sources of agency problems.